2021
DOI: 10.1002/adfm.202101843
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐Sample and Intra‐Sample Variability in Electronic Properties of Methylammonium Lead Iodide

Abstract: While the challenges associated with the stability of metal halide perovskites are well known and intensely studied, variability in electronic properties represents an equally significant, yet seldom studied, challenge that could potentially slow or inhibit the commercial viability of these systems. In this work, the contactless characterization technique time-resolved microwave conductivity (TRMC) is used to quantify the variability in electronic properties of the prototypical perovskite, methylammonium lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…It should be noted that unlike electrical measurements, where charges must travel ≈µm to be extracted and hence detectable, TRMC is a local probe, so the relationship between mobility and morphology can be distinct. [ 65 ] More importantly, these results provide direct evidence that changes in carrier mobility in self‐n‐doped PDIs are relatively unsubstantial and cannot account for the large increases in electrical conductivity typically observed in these materials following annealing. This result also provides indirect evidence that doping primarily generates free carriers, though future work in this area could establish the branching ratio between bound states and free carriers.…”
Section: Resultsmentioning
confidence: 98%
“…It should be noted that unlike electrical measurements, where charges must travel ≈µm to be extracted and hence detectable, TRMC is a local probe, so the relationship between mobility and morphology can be distinct. [ 65 ] More importantly, these results provide direct evidence that changes in carrier mobility in self‐n‐doped PDIs are relatively unsubstantial and cannot account for the large increases in electrical conductivity typically observed in these materials following annealing. This result also provides indirect evidence that doping primarily generates free carriers, though future work in this area could establish the branching ratio between bound states and free carriers.…”
Section: Resultsmentioning
confidence: 98%
“…[32] It is important to reiterate that the data presented in Figure 3 is the mean of three identically processed samples for every condition and that TRMC measures electronic properties over a macroscopic area (defined by laser spot size). We know that microstructure [29,35] and phase [44] have a significant impact on charge transport in this class of materials, so we would expect differences in parameters depending on processing, but we interpret the presented values as the representative average for each composition.…”
Section: Role Of A-site Composition On Electronic Propertiesmentioning
confidence: 99%
“…We have shown that, for our processing and measurement protocols at least, surface morphology is not strongly correlated with ϕΣμ. [ 29 ] Another possibility is that the average structure of the perovskite is modified, and the electronic structure also changes. A simple way to quantify the structure of perovskites is using the Goldschmidt tolerance factor, [ 60 ] defined by Equation ().TF=rnormalA+rnormalX2false(rnormalB+rnormalXfalse)…”
Section: Relationship Between Properties In Lead Iodide Perovskite Th...mentioning
confidence: 99%
See 2 more Smart Citations